A Review of the Jumping Spider Fauna (Araneae: Salticidae) of Chile - Richardson, Barry J. (Zootaxa, 2010)
The salticid fauna of Chile is relatively small, consisting of 21 known species in eight genera. The male and female morphology of each species for which material was available is shown. Two new species, Dendryphantes villarrica n. sp. and Euophrys flordellago n.sp. are described. Euophrys pehuenche Galiano, 1968 is synonymised with Euophrys rapida C. L. Koch, 1846. As well, three little known species, Euophrys saitiformis Simon, 1901, Euophrys laetata Simon, 1904 and Euophrys rapida C. L. Koch, 1846 are redescribed from the types. The female of Dendryphantes fulvipes is described for the first time. Several earlier described species remain unidentifiable from modern material. Eighteen names are listed as species inquirenda as the descriptions are inadequate and the location of the types unknown. Keys to the genera and known species are provided. Remarks on the biology and distribution of each species are given.La fauna chilena de saltícidos es relativamente pobre, siendo de 21 especies ubicadas en ocho géneros. Se presenta la morfología del macho y de la hembra de cada una de las especies a las cuales se disponía de material. Se describen dos especies nuevas: Dendryphantes villarrica n. sp. y Euophrys flordellago n.sp. Euophrys pehuenche Galiano, 1968 es reducido a estado de sinónimo con Euophrys rapida C.L. Koch, 1846. Adicionalmente, tres especies poco conocidas― Euophrys saitiformis Simon, 1901, Euophrys laetata Simon, 1904 y Euophrys rapida C.L. Koch, 1846― se vuelven a describir a base de los ejemplares tipos. Por primera veza se decribe la hembra de Dendrophantes fulvipes. Varias especies, posiblemente legítimas, se desconocen en colecciones modernas. Se considera 18 nombres como species inquirenda, ya que sus descripciones originales son inadecuadas y se desconoce la ubicación de los ejemplares tipos. Se presentan llaves para la identificación de los géneros y de las especies conocidas. Se aporta información sobre la biología y distribución de cada especie.